Pengaruh Gaya Kepemimpinan Otoriter Dan Lingkungan Kerja Non Fisik Terhadap Kinerja Pegawai UPTD PUPR Pematang Siantar - Evans Alderton Sihaloho; Rosita Manawari Girsang; Darwin Damanik (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
Certain leadership style factors can be one of the factors that influence employee performance. Employee performance can increase or decrease and can be influenced by authoritarian leadership style and the non-physical work environment in the office. Therefore, researchers are interested in knowing the influence of an authoritarian leadership style and a non-physical work environment on the performance of employees of the Regional Technical Implementation Unit for Public Works and Spatial Planning in Pematang Siantar. Researchers collected data on 50 employees as a sample of 102 employees. The analytical method used is multiple linear regression analysis. The results of the research show (1) There is a positive and significant influence between authoritarian leadership style on employee performance. (2) There is no positive and significant influence between the non-physical work environment on employee performance. (3) There is an influence of authoritarian leadership style and non-physical work environment simultaneously and together on employee performance.